(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Learning motivation is the key factor of school success. The process of acquiring new knowledge requires motivation from the side of the student, and at the same time, dealing with new tasks triggers the experience of success (Réthy, 2002). Motivation is modified according to internal dynamic driving forces and external factors; which means that it rests on the cognitive, affective, effective interaction self-regulation system of the student and his/her environment (Réthy, 2001). The social environment can influence learning motivation (Fejes, 2015). Fejes’ Goal orientation (2015) and Kozéki and Entwistle’s School motivation (1986) questionnaires served as a base for our research. The research involved five vocational training schools, 445 students, who studied in the 9th and 11th grades in spring 2019. The results contribute to understanding students’ learning motivation in vocational training schools, and point to their developmental potentials.